2021
DOI: 10.3390/ijms22147599
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Distribution in Human Sperm Heads and Its Relation to Sperm Nuclear Morphology: A New Marker for Male Factor Infertility?

Abstract: Infertility is a problem affecting an increasing number of couples worldwide. Currently, marker tests for male factor infertility are complex, highly technical and relatively subjective. Up to 40% of cases of male factor infertility are currently diagnosed as idiopathic therefore, there is a clear need for further research into better ways of diagnosing it. Changes in sperm telomere length have been associated with infertility and closely linked to DNA damage and fragmentation, which are also known to be relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…Many studies suggest that telomere length is significantly associated with sperm count, concentration, motility, and morphology [43][44][45]52,53,68,69]. We found that STL is significantly shorter in infertility patients and is strongly inversely correlated with various semen parameters.…”
Section: Discussionsupporting
confidence: 48%
“…Many studies suggest that telomere length is significantly associated with sperm count, concentration, motility, and morphology [43][44][45]52,53,68,69]. We found that STL is significantly shorter in infertility patients and is strongly inversely correlated with various semen parameters.…”
Section: Discussionsupporting
confidence: 48%
“…The disruption of nuclear lamina has a global effect on the compaction of chromatin domains and their nuclear positioning [109]. Telomere positioning at the nuclear periphery is a key feature of genome organization in yeast, Drosophila, and a subset of mammalian cell types [110][111][112][113].…”
Section: Nuclear Topology and Epigenetics Of Telomeresmentioning
confidence: 99%
“…Telomere distribution in this case may suggest infertility, but it may also be the cause of infertility rather than just a symptom in an infertile man. Given that telomeres are histone-bound and positioned near nuclear boundaries, it is hypothesized that this may have a functional effect on the process of fertilization [27].…”
Section: Introductionmentioning
confidence: 99%